The participation of digital users in the tourism sector - analysis of comments on Turismo do Centro’s social networks - Vendeiro, Ana; Bonixe, Luís (Aprender, 2024)
The emergence of social networks has changed the way we relate to each other and to institutions. The possibility of individuals being both producers and consumers of content has posed new challenges at various levels, through the increase in authors and protagonists in the public space. The tourism sector has not been immune to these changes, and there are several dimensions in which it uses digital communication, whether to communicate with its customers, promote its products or receive contributions from users of the various platforms. In this article, we start from Nico Carpentier’s theoretical contribution on the concept of participation in the digital space, as distinct from access and interaction, and try to understand how users make use of this possibility in the context of the social networks of an organization in the tourism sector. The analysis of the comments published on Turismo do Centro’s Facebook and Instagram accounts revealed that users tend to interact with the institution and less to participate, considering Carpentier’s contribution.